Colorectal Cancer Screening Based on Fecal Immunochemical Test and Risk Assessment: A Population-based Study Including Two Million Participants in China - Dong Hang; Chen Zhu; Xiaolin Yang; Jinjin He; Huizhang Li; Tingting Pan; Le Wang; Shi Wang; Wei Wu; Jieming Zhong; Weiwei Gong; Meng Zhu; et al. (Journal of Epidemiology)
Background: The fecal immunochemical test (FIT) has been widely used in colorectal cancer (CRC) screening, yet the practical performance of FIT combined with questionnaire-based risk assessment (QRA) remains undetermined. Moreover, risk factors for distinct CRC precursors identified in screening have been rarely compared. Methods: This study was based on a population-based CRC screening in China, with 2,120,340 participants completing both FIT and QRA. Those with positive FIT or high QRA scores were recommended for colonoscopy. We reported the compliance, detection rate, and colonoscopy workload according to FIT and QRA results. We also explored risk factors for conventional adenomas and serrated polyps. Results: The compliance rate of colonoscopy in the subgroup of FIT (+) and QRA (+) was 41.4%, higher than the rates in FIT (+) and QRA (−), as well as FIT (−) and QRA (+), which were 38.7% (P < 0.001) and 16.4% (P < 0.001), respectively. The corresponding detection rates of advanced neoplasia were 18.2%, 13.2%, and 9.3% (all P < 0.001), respectively. Moreover, the required numbers of colonoscopies to detect one advanced neoplasia in the three subgroups were 5.5, 7.6, and 10.8, respectively. Increased body mass index, smoking, alcohol consumption, red meat intake, and type 2 diabetes were associated with higher risk of advanced adenomas and advanced serrated polyps, whereas vegetable intake was inversely associated with advanced adenomas. Conclusion: FIT and QRA can synergistically identify individuals at high risk of colorectal advanced neoplasia, with those testing positive for both deserving immediate attention. Modifiable factors were identified to complement screening for preventing CRC precursors.